2013
DOI: 10.3390/molecules18089850
|View full text |Cite
|
Sign up to set email alerts
|

Breathing Some New Life into an Old Topic: Chalcogen-Nitrogen π-Heterocycles as Electron Acceptors

Abstract: Recent progress in the design, synthesis and characterization of chalcogennitrogen π-heterocycles, mostly 1,2,5-chalcogenadiazoles (chalcogen: S, Se and Te) and their fused derivatives, possessing positive electron affinity is discussed together with their use in preparation of charge-transfer complexes and radical-anion salts-candidate building blocks of molecule-based electrical and magnetic functional materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 199 publications
(336 reference statements)
0
63
0
Order By: Relevance
“…In our study we use both traditional building blocks reviewed previously by us and by other authors and extended list of donor groups that includes some new previously unexplored fragments. Based on our recent investigations and the works of other researchers 7,[14][15][16][17][18][19][20][21][22][23][24] six variants of A-fragments (A-block) which have showed good characteristics were selected for the present study: [1,2,5]thiadiazolo [3,4-c] [3,4-c]pyridazine. The general formula for these derivatives is represented in Scheme 1.…”
Section: Building Blocks For D-a-π-a Featured Organic Sensitizersmentioning
confidence: 99%
“…In our study we use both traditional building blocks reviewed previously by us and by other authors and extended list of donor groups that includes some new previously unexplored fragments. Based on our recent investigations and the works of other researchers 7,[14][15][16][17][18][19][20][21][22][23][24] six variants of A-fragments (A-block) which have showed good characteristics were selected for the present study: [1,2,5]thiadiazolo [3,4-c] [3,4-c]pyridazine. The general formula for these derivatives is represented in Scheme 1.…”
Section: Building Blocks For D-a-π-a Featured Organic Sensitizersmentioning
confidence: 99%
“…According to the gas-phase (U)B3LYP/6-31+G(d) calculations, the first adiabatic electron affinity (EA) of compounds 5g and 5c are 1.55 and 1.93 eV, respectively, as compared with 0.22 eV for 1,2,5-selenadiazole and 1.06 eV for 2,1,3-benzoselenadiazole (10). [7] In the potential range 0 --2 V, the cyclic voltammogram (CV) of 5g contains three reduction peaks Ep Ep 1C = −1.40 V. [30] For both 5g and 5c the first reduction peak is H decoupling during acquisition. Spectra were acquired with recycle intervals of between 5 and 55 s, depending on the longitudinal relaxation time of the samples.…”
Section: Structure Elucidation By Xrd and 77 Se Nmrmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Amongst 1,2,5-chalcogenadiazoles the best studied are the sulfur derivatives [1][2][3][4]7,10,11] though there are scattered reports on the selenium analogues, [2,4,7,[12][13][14] whereas chemistry of 1,2,5-telluradiazoles is only emerging. [4][5][6][7]15,16] Very recent interest to these compounds, especially fused with benzene and heterocyclic rings, is due to their actual or potential applications as building blocks in organic functional materials such as light emitters, solar cells, synthetic metals, as well as drugs for preventive and therapeutic medical treatment and fluorescent imagine probes. [1,4,7,13,14,17] Recently, it was shown that many classes of chalcogennitrogen π-heterocycles possess positive electron affinity (EA) making them suitable precursors for thermodynamically stable radical anions (RAs) which are possible building blocks for magnetically-active functional materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations